2014
DOI: 10.1128/aac.02573-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of an IncA/C Multidrug Resistance Plasmid from Escherichia coli and Klebsiella Isolates from Intensive Care Unit Patients and the Utility of Whole-Genome Sequencing in Health Care Settings

Abstract: The IncA/C plasmids have been implicated for their role in the dissemination of ␤-lactamases, including gene variants that confer resistance to expanded-spectrum cephalosporins, which are often the treatment of last resort against multidrug-resistant, hospital-associated pathogens. A bla FOX-5 gene was detected in 14 Escherichia coli and 16 Klebsiella isolates that were cultured from perianal swabs of patients admitted to an intensive care unit (ICU) of the University of Maryland Medical Center (UMMC) in Balti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 70 publications
0
23
0
Order By: Relevance
“…Other countries, such as Australia, Canada, and Italy, reported other plasmid types, including IncFII, IncR, IncP, and L/M, in Citrobacter spp . Recent studies have reported the increased isolation of A/C plasmids in Enterobacteriaceae species, including E. coli , K. pneumoniae , and Salmonella spp . Most isolates reported in our review here were clinical isolates from humans; few studies evaluated here addressed carbapenemases and plasmid replicon groups in animal and environmental isolates (Fig.…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 85%
“…Other countries, such as Australia, Canada, and Italy, reported other plasmid types, including IncFII, IncR, IncP, and L/M, in Citrobacter spp . Recent studies have reported the increased isolation of A/C plasmids in Enterobacteriaceae species, including E. coli , K. pneumoniae , and Salmonella spp . Most isolates reported in our review here were clinical isolates from humans; few studies evaluated here addressed carbapenemases and plasmid replicon groups in animal and environmental isolates (Fig.…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 85%
“…coli : i) ST1434, previously detected in Mexico in two strains recovered from water and human feces which were categorized as non-pathogenic [34]; ii) ST216, identified among ESBL-producing E . coli strains of fecal origin in the US [35] and Europe [36], and as the most prevalent ST in IMP-producing strains recovered from gulls feces in Australia [37]; and iii) ST5001, a singleton newly described in this study. Both ST1434 and ST216 belong to clonal complex CC10, from which several KPC-producing isolates have previously been described, although only in surveillance culture studies in Israel [38].…”
Section: Discussionmentioning
confidence: 99%
“…The first IncA/C plasmids were isolated from aquatic host species, including the fish pathogen Aeromonas salmonicida (6), and pandemic strains of Vibrio cholerae (7,8). However, recently, there has been a significant increase in the isolation of IncA/C plasmids from Enterobacteriaceae, including Salmonella (9), Klebsiella pneumoniae (10), and Escherichia coli (11).…”
mentioning
confidence: 99%